A comparative analysis of confiscating vehicles used in drunk-driving (Academic Journal of Internal Affairs, 2018)
The author provides a comparative overview of the legal background and practice of confiscating vehicles used for DUI.
Keywords: drunk-driving; regulation; confiscation